Kajian Strategi Daya Saing dan Inovasi Produk PT Indofood Sukses Makmur Tbk - Dewi Mas Arumsari; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This journal examines the strategic approach to enhancing competitiveness and product innovation at PT Indofood Sukses Makmur Tbk, a leading food and beverage company in Indonesia. The study outlines the company’s vision, mission, and long-term objectives, proposing strategies aimed at strengthening its market position through innovation and operational efficiency. Key strategies such as product diversification, quality enhancement, and research and development (R&D) are identified to build and sustain competitive advantage. The analysis draws on recent strategic theories, including the Competitive Advantage Theory (Zeng et al., 2021), Disruptive Innovation Theory (Morris et al., 2019), and the Resource-Based View (RBV) (Chirico et al., 2020). The paper concludes with practical recommendations for Indofood to maintain its industry leadership and continue innovating in response to evolving consumer demands and competitive pressures.